Pregnancy and Venous Thromboembolism - Barco, Stefano; Nijkeuter, Mathilde; Middeldorp, Saskia (Seminars in Thrombosis and Hemostasis, 2013)
Pregnancy and the postpartum period are associated with an increased risk of venous thromboembolism (VTE), which complicates 1 to 2 of 1,000 pregnancies and represents a leading cause of mortality during pregnancy in developed countries. Strong evidence for the management of pregnancy-related VTE is missing, mostly because pregnant women have been excluded from all major trials investigating different diagnostic tools and treatment regimens. Nevertheless, proper evaluation of the involved risk factors is mandatory to reduce the incidence of pregnancy-related VTE and improve outcomes. Low-molecular-weight heparins are considered as a first-line option in the management of pregnancy-related VTE. With regard to future research, there is a need for methodologically strong studies in pregnant women, especially with respect to risk stratification, optimal heparin doses, usefulness of anti-FXa levels and their correlation with clinical outcomes, and correct management of anticoagulation during delivery.
Keywords: pregnancy; venous thrombosis; pulmonary embolism; hemostasis; anticoagulants